PENILAIAN PESERTA TERHADAP KINERJA TUTOR, DAN HASIL TUTORIAL DAN BIAYA TUTORIAL PADA TUTORIAL TATAP MUKA DI UNIVERSITAS TERBUKA - Herman Herman (LPPM Universitas Terbuka, 2010)
This article aims to report students perception on face to face tutorials at Universitas Terbuka. Three latent variables which are tutors performance, tutorial result and tutorial cost were investigated. The respondents were 100 students from Jakarta and 100 students from Bandung where each location consisted of 50 students from Faculty of Education and 50 students from Faculty of Economics and Faculty of Social Sciences. Data was analyzed by using Factor Analysis, Multivariate Analysis of Variance, Univariate Analysis of Variance, and t-test.The results were: (1) The majority of students gave positif respon to all of the statements, (2) 10 out of 48 staments on students perception have to be considered by UPBJJ-UT and UT management because 10%-13% of respondents gave low scores, (3) Student from Faculty of Economics and Sicial Science at UPBJJ-UT Bandung had higher scores in tutorial result than their colleagues from Faculty of Education (4) Student from Faculty of Education at UPBJJ-UT Jakarta felt that tutorial cost was more expensive than their colleagues from other faculties, (5) There was no significant difference between students from UPBJJ-UT Jakarta and Bandung based on their perceptions on tutors performance, tutorial result, and tutorial cost.